Whether perception or expert based paradigm? assessing scenic beauty of nature based landscape - Othman, Jamilah; Rosli, Nur Shazwani (International Journal for Research in Emerging Science and Technology, 2014)
In general, studies on scenic beauty assessment observed to flourish tremendously, due to the advance of knowledge in science, technology and socio-politics. Since then, many and new theories on the issue have been rigorously established in the West. Among these are the expert and perception based paradigms. Both paradigms received positive acceptance over the last century. Looking at this, it is unlikely to say, whether the expert is better than the perception or vice versa. The former is found to dominate the environmental management practice, while the latter is highly accepted among the researchers in the studies of landscape preference. The assessment’s procedure using the perception-based has solely relied on public’s participation, while the expert based requires the trained professionals from the disciplines of art and design, landscape architecture, planning, architecture, ecology, psychology, geography and many more. In principle, both authorities recognise the biophysical features of a landscape (e.g. greenery, water element, landform and etc.) as attributes to assess scenic beauty of nature based landscapes. The major difference between the two can be detected in the scenic beauty assessment’s procedures presented in the works of Clay and Daniel (2001) and Pierskalla &associates (2007). This paper describes the approach used in each paradigm having concentrated on the techniques of assessing scenic beauty of nature based landscapes. The insights provide a basic knowledge to young researchers with similar research interest and to the Malaysian authority that has concerned for preserving the natural beauty of its unique ecosystems.